A REVIEW IN GENOMIC AND PRECISION MEDICINE ON CANCER IN INDONESIA : genomic and precision medicine - widjaja, sry suryani; Rusdiana; Yudhistira, Ashri (International Journal of Ecophysiology, 2024)
Genomic and precision medicine has been a new target on oncology field, as with the genomic study, we can develop the precised medicine. This studies was made to find the development of research on genomic and precision medicine on cancer in Indonesia. This study is conducted systematically to explore an update on genomic and precision medicine on cancer in Indonesia based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) to extend this scoping review. After further research and exploration, we found 7 literatures that shares the same inclusion criteria. From these seven literatures, we found that there is a significant development in this field of research, however most studies are about the detection of gene and has not develop research in treament or rehabilitation. Indonesia is a capable country to develop this field of research. With that being said, the encouragement and empowerment of researchs in Indonesia on genomic and precision medicine must be enchanced.